Explaining the Transformation of Ethical Vegans: Is Mezirow's Theory Adequate? - Barbara L. McDonald (Adult Education Research Conference, 1999)
This paper explores the adequacy of Mezirow's transformation theory to describe the transformational learning of ethical vegans. A critical reading of the participants' narratives revealed that a temporal understanding of power is needed. Transformation theory failed to account for the power of normative ideologies to undermine the emancipatory learning and praxis of ethical vegans over time.